Formation of Composite Polyaniline and Graphene Oxide by Physical Mixture Method - Vargas,Ludmila Resende (2017)
ABSTRACT: The development of polyaniline and graphene oxide composites aims to join the unique properties of each material for aerospace applications. The present paper demonstrates an easy and quick method, compared to the ones found in the literature, to obtain a composite made with polyaniline doped with dodecylbenzenesulfonic acid, a combination commonly called polyaniline, and graphene oxide. Nowadays, the most common studied methods are electrochemistry and in situ chemical polymerization. Differently from these methods, the films were obtained by a physical mixture of equimolar suspension of graphene oxide (4 mg/mL) with 3 concentrations of polyaniline powder: 25; 50 and 75%, being compared to pure graphene oxide and polyaniline. The morphology and structure behavior of all the films were studied, besides the bonding nature between both materials. The films were analyzed by scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and differential scanning calorimetry. The apparent interaction between graphene oxide corrugated sheets and polyaniline grains was verified by scanning electron microscopy images. It can be noticed, as the concentration of polyaniline increases, that more polymer was entrapped. To prove the formation of polyaniline/graphene oxide composite, X-ray diffraction and Fourier transform infrared spectroscopy techniques demonstrated the changes on graphene oxide crystallographic plans and on the chemical bonding between polyaniline and graphene oxide, suggesting an interaction between polyaniline and graphene oxide, especially in the composite with 50% polyaniline/50% graphene oxide. Differential scanning calorimetry was used to highlight this effect through the increase in thermal stability. The method of physical mixture was efficient to obtain the polyaniline/ graphene oxide composites.